Deposition and Mineralogical Characteristics of Atmospheric Dust in relation to Land Use and Land Cover Change in Delhi (India). (26th August 2014) - Kumar, Bablu; Verma, Kopal; Kulshrestha, Umesh
Abstract : This study highlights that the increasing urbanization and industrialization in Delhi are responsible for higher fluxes of atmospheric dust and its chemical constituents. Delhi has experienced a drastic change in land use and land cover area during the past two decades. Road lengths of the city have increased by 76% from 1985 to 2011. The number of mobile vehicles has reached 80, 52, 508 in 2014 from 24, 32, 295 in 1994. The industrial units in Delhi have increased by 39.54% in 2011 as compared to 1994 value. Atmospheric dust which is originated from soil in this region becomes carbon rich due to interaction of suspended soil with atmospheric pollutants. Emissions of carbonaceous aerosols from coal and petroleum combustions are mainly responsible for silica dominated soil dust transforming into carbon rich particulate matter. Such dust may play very important role in the atmosphere having significant influence on human health, global warming, climate change, radiative forcing, visibility, and cloud formation. It is expected that if the rate of development remains the same, green cover of the city invariably will be sized down in order to meet the demand of housing, transportation, industries, and so forth in proportion to the rising population.